Synthesis and Characterization of [2+2] Cu(II) Macrocyclic Schiff Base Comp
[2+2]Cyclocondensation of L22py = N-(2-pyridylmethyl)-N-(2-aminoethyl)-1,2-diaminoethane, L23py = N-(2-pyridylmethyl)-N-(2-aminoethyl)-1,3-diaminopropane, L33py = N-(2-pyridylmethyl)- N-(3-aminopropyl)-1,3-diaminopropane